Geographical distribution of tourist sites in Najaf Governorate and study of available potentials for their development - Abdullal Azeez Ibtihal; Ahmed Bneen Nassr; Azeez Bjwo Amtihan (E3S Web of Conferences)
Tourism in Iraq in general and Najaf Governorate in particular has occupied a distinguished position among other activities, in addition to its civilizational and cultural effects due to the increase in demand and the increase in tourists, and thus increased interest in the tourism movement that provides a resource with hard currencies and reduces the unemployment rate and develops and develops vast regions.Therefore, the research aimed to reveal the tourist sites in the governorate and how to develop and develop them. The research structure dealt with three topics, the first of which came with the theoretical framework of the research from the problem, importance and goal, then stating the concept of tourism and its importance. The second topic focused on highlighting the most important tourist sites in the governorate that witnessed wide demand, especially at the present time, and were identified using the (GIs) program. Then the third topic dealt with the potential, whether natural or human, affecting tourism in Najaf Governorate, after identifying the strengths and weaknesses using SWOT analysis. Then the research came out with a set of conclusions and recommendations that can be applied by decision-makers to develop tourism more in the governorate.